Colored Fields of Light Surrounding Living Organisms: Responses to Magnetic Fields and Mental Attention-A Unique Case Study - Ryd, Marie; Ahn, Andrew; Andersson, Göte (Journal of Scientific Exploration, 2025)
A 14-year-old boy reported perceiving transparent colored light fields surrounding human and animal bodies. With drawings and verbal descriptions, he explained the phenomenon in detail. The left side of the body was covered with a transparent blue, and the right side was covered with transparent red, reaching 0.5–2 cm outside the skin. The blue field was attracted towards the north pole of a bar magnet and repelled from the south pole in 127/130 randomized, single-, and double-blind trials (30). The red field showed opposite results in a few pilot experiments. An additional outer rainbow-colored field extended 20–50 cm from the body responded to the magnet in the same way as the inner field in 50/50 trials. Notably, these fields seemed responsive to cognitive focus, with thin red and blue spirals emerging at different heights on each side of the body. The boy also identified “thought-forms” as cognitive-dependent extensions of the fields at the ends of these spirals. In an extraordinary example, a right-leg amputee secretly visualized having a healthy leg and foot. The boy reported seeing a healthy limb in red light projecting as an extension of the right-sided red “Inner field”. These initial results suggest: 1) the boy’s perceptions are not mere illusions, 2) the body possesses polar asymmetry along the left/right axis, and 3) significant influences of cognitive states on these fields exist, even over distances beyond the limits of the body. This case study is remarkable in its level of detail (including original illustrations) and in the experiments performed to assess their validity. We call for interdisciplinary exploration into three key areas: a) unraveling the nature and sensory basis of this extraordinary perception; b) uncovering potential physiological or physical processes enabling such experiences; and c) understanding the mechanisms facilitating the generation of these extended fields, as influenced by cognitive states.